Mandibular Actinomyces osteomyelitis complicating florid cemento-osseous dysplasia: case report - Edwards Sean P; Lebar Bill; Newton Duane W; Harms Paul W; Smith Miller H; Aronoff David M (BMC Oral Health, 2011)
Abstract Background Apart from neoplastic processes, chronic disfiguring and destructive diseases of the mandible are uncommon. Case Presentation We report, perhaps for the first time, the simultaneous occurrence of two such conditions in one patient, in a case that emphasizes the importance of bone biopsy in establishing the correct diagnosis. Florid cemento-osseous dysplasia (FCOD) is a chronic, disfiguring condition of the maxillofacial region. This relatively benign disease is primarily observed in middle-aged women of African ancestry. Cervicofacial actinomycosis is an uncommon and progressive infection caused by bacilli of the Actinomyces genus that typically involves intraoral soft tissues but may also involve bone. The accurate diagnosis of actinomycosis is critical for successful treatment. A diagnosis of osteomyelitis caused by Actinomyces bacteria was diagnosed by bone biopsy in a 53 year-old African-American woman with a longstanding history of FCOD after she presented with a new draining ulcer overlying the mandible. Conclusions Clinicians should be aware of the possibility of actinomycosis arising in the setting of FCOD, and the importance of bone biopsy and cultures in arriving at a definitive and timely diagnosis.